Hybrid Culture in Indonesian EFL Textbooks: Policies and Pedagogical Implications - Jimmy Sapoetra (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2023)
Hybrid Culture is a new term which reflects the diversity and complexity of the world culture existing today. The term hybrid culture refers to the mixture of several kinds of culture blended or integrated into one new culture which has the characteristics of the old and new culture it represents. In the context of EFL learning in Indonesia, many EFL textbooks do not really cover the hybridity of the culture which creates the pedagogical implications in the future of education. The majority of the textbooks either focus on the local or target culture. They do not emphasize the importance of the students to understand that culture is not single-handedly original in its nature but consists of many external factors. This study attempts to examine such a phenomenon. The data were taken from 3 (three) local EFL textbooks used in some high schools in Indonesia. The researcher uses the Content Analysis method with the cultural content evaluation by Byram and Morgan (1994) and Kilickaya (2004). They proposed a qualitative evaluation checklist with a list of criteria for examining the extent and methods of how culture is presented. There are nine categories from the checklist, namely- social identity and social groups, social interaction, belief and behavior, socio-political institutions, socialization and the life-cycle, national history, national geography, national cultural heritage, stereotypes and national identity (Byram & Morgan, 1994). Then the results were compared and it was found that the textbooks do not clearly represent the hybrid culture in their content.